Výběr zaměstnanců a proces adaptace ve vybrané společnosti - Fialová, Pavla (Vysoké učení technické v Brně. Fakulta podnikatelská, 2021)
Diplomová práce je zaměřena na výběr zaměstnanců a proces adaptace ve vybrané společnosti. V teoretické části jsou vysvětleny činnosti související s výběrem a adaptací zaměstnanců. Prostřednictvím analýzy současného stavu a provedeného výzkumu jsou doporučeny návrhy na zlepšení s cílem lepšího fungování společnosti.

The thesis is focused on the selection of employees and the adaptation process in the selected company. The theoretical part explains the activities related to the selection and adaptation of employees. Through the analysis of the current situation and the research conducted, suggestions for improvement are recommended in order to improve the functioning of the company.
Selection and Adaptation of Employees in a Selected Company
Keywords: výběr zaměstnanců; adaptace; výběrové řízení; zaměstnanec; selection of employees; adaptation; selection procedure; employee